New insights into the identities of the elasmobranch fauna of Sri Lanka - Fernando, Daniel; Bown, Rosalind M. K.; Tanna, Akshay; Gobiraj, Ramajeyam; Ralicki, Hannah; Jockusch, Elizabeth L.; Ebert, David A.; Jensen, Kirsten; Caira, Janine N. (Zootaxa, 2019)
Identities of elasmobranchs from Sri Lanka encountered during collections conducted in an intensive nine-day survey of fish markets and landing sites at 11 localities in the North Western, Northern, and Eastern Provinces in March of 2018 were assessed. In total, 111 specimens representing 34 elasmobranch species were examined. Sequence data for the NADH2 gene were generated for all specimens. Independent Neighbor-Joining analyses, which included data for related taxa, were conducted for 25 subgroups of elasmobranchs to help confirm specific identifications. Five of the 34 species encountered are likely new to science. These consist of one species each of the batoid genera Brevitrygon, Narcine, and Torpedo, and the selachian genera Centrophorus, and Chiloscyllium. The specific identities of 12 species previously known to occur in Sri Lanka are updated to conform to current taxonomy; four of these (Gymnura cf. poecilura 2, Carcharhinus cf. limbatus, Echinorhinus sp. 1, and Iago cf. omanensis 1) represent what appear to be undescribed species reported previously from other localities. Three species (Maculabatis arabica, Acroteriobatus variegatus, and Centroscymnus owstonii) are reported from Sri Lanka for the first time; the latter species also represents the first documented record of this genus and family for the island nation. One of the two specimens on which the recent description of the new species of Planonasus indicus was based was also collected as part of this survey. Although some of the species confirmed to occur in Sri Lanka have also been found in India, others were previously known only from the Persian Gulf, Gulf of Oman, or localities in Southeast Asia. The high amount of novelty discovered as a result of a survey of such short duration emphasizes the importance of more intensive survey efforts in this region now that the civil unrest that precluded such work for nearly three decades has come to an end.